1986
DOI: 10.1111/j.1469-8137.1986.tb00617.x
|View full text |Cite
|
Sign up to set email alerts
|

THE POTENTIAL FOR EVOLUTION OF SALT (NaCl) TOLERANCE IN SEVEN GRASS SPECIES

Abstract: SUMMARYThe seedling root growth of Agrostis stolonifera L., Agrostis capillaris L., Holcus lanatus L., Loliiim perenne L., Dactylis glomerata L., Festuca rubra L. and PuccineUia distans (L.) Parl. was examined after 14 d of immersion in dilute nutrient solutions containing 0, 150, and 250 mol m-'' NaCl. Root growth of all species was significanfly reduced by increasing NaCl concentration.Samples of 10000 to 20000 seeds of each species were then screened for ability to root in solution cultures at NaCl concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0
1

Year Published

1990
1990
2008
2008

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(34 citation statements)
references
References 18 publications
(23 reference statements)
4
28
0
1
Order By: Relevance
“…However, the data from literature confirm the fact that within the group of lawn grasses Lolium perenne tolerates salinity relatively well (Ashraf et al 1986, Wysocki 1994, Pawluśkiewicz 2000, Xiaofang et al 2000, Hujun 2001, Yongqin et al 2003, Stawicka et al 2006.…”
Section: Resultssupporting
confidence: 58%
See 3 more Smart Citations
“…However, the data from literature confirm the fact that within the group of lawn grasses Lolium perenne tolerates salinity relatively well (Ashraf et al 1986, Wysocki 1994, Pawluśkiewicz 2000, Xiaofang et al 2000, Hujun 2001, Yongqin et al 2003, Stawicka et al 2006.…”
Section: Resultssupporting
confidence: 58%
“…Horst and Dunning (1989) in the studies on Lolium perenne, and Ashraf et al (1986) in the studies on 7 different grass species found out clear inhibition of the growth of germinal roots under the effect of increasing concentration of NaCl in the environment. On the other hand, in the studies by Ashraf et al (1986), the seedlings of Lolium perenne in the control conditions had longer roots than Festuca rubra roots, but the reduction of their growth under the effect of salinity of 150 and 250 M × m -3 NaCl was also higher than in Festuca rubra. As follows from the studies, salinity inhibits the elongation growth of grass coleoptile the most although in the control conditions those organs grew faster than the roots (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ecotype formation seems to be a rapid and successful process (e.g. Al-Hiyaly et al, 1990) which is not always related to any genetic potential for tolerance present in the initial population (Gartside & McNeilly, 1974 ;Ashraf et al, 1986). In Chloris gayana, salinity tolerance was not increased by five successive generations of artificial selection towards the most tolerant individuals (Malkin & Waisel, 1986).…”
Section: mentioning
confidence: 99%